Hexagonal hierarchical cartogram: Towards a thematic map of Brazil - Colares Barreto, Moises; Kosminsky, Doris; Esperança, Claudio (InfoDesign, 2018)
The popularity and availability of digital tools has boosted the use of thematic maps in infographics and data visualizations. Unlike general purpose maps, thematic maps are aimed at communicating the spatial distribution of a particular topic or theme, such as population density, voter preference or income. Since thematic maps have been more often studied and tailored for European and North American countries, some of them need adjustment to properly represent Brazilian states, according to their needs. The aim of this paper is to present the hexagonal hierarchical cartogram, which represents Brazilian states in a normalized geographical format using single-hue color scales to show magnitude. We demonstrate its use by mapping average grades obtained by students of all Brazilian states in a national exam called ENEM (Exame Nacional do Ensino Médio).